Analysis of the Book "Ilmu Sharaf Untuk Pemula" by Abu Razin and Ummu Razin Based on Methods and Techniques of Learning - Pein, Maulana; Sastra, Ahmad; Indra, Hasbi (EDUCATIO : Journal of Education, 2024)
The science of Sharaf focuses on the study of word transformation in Arabic, emphasizing three core concepts: fi'il (verb), ism (noun), and harf (particle). Various reference books have been published on the subject, with al-Jurumiyah being one of the most well-known. In addition to traditional Arabic texts, there are also resources available in Indonesian that present the science of Sharaf in a concise and accessible manner. One such book is Sharaf for Beginners by Abu Razin and Ummu Razin. This study aims to analyze this book through a qualitative approach, employing descriptive analytical data analysis. The findings indicate that the book utilizes two primary teaching methods: the manhaji method and the tashrif method. From a technical perspective, the book incorporates three distinct techniques, which are categorized as mind mapping, descriptive, and testing techniques. These methods and techniques serve to enhance the understanding of Sharaf for beginners and provide a structured approach to learning the subject. The implications of this study suggest that the book effectively combines traditional and modern methods to facilitate a comprehensive learning experience for its readers.